Differing rates of antibody acquisition to merozoite antigens in malaria : Implications for immunity and surveillance - McCallum, Fiona J.; Persson, Kristina E.M.; Fowkes, Freya J.I.; Reiling, Linda; Mugyenyi, Cleopatra K.; Richards, Jack S.; A. Simpson, Julie; Williams, Thomas N.; Gilson, Paul R.; Hodder, Anthony N.; Sanders, Paul R.; Anders, Robin F.; et al. (Journal of Leukocyte Biology, 2017)
Antibodies play a key role in acquired human immunity to Plasmodium falciparum (Pf) malaria and target merozoites to reduce or prevent blood-stage replication and the development of disease. Merozoites present a complex array of antigens to the immune system, and currently, there is only a partial understanding of the targets of protective antibodies and how responses to different antigens are acquired and boosted. We hypothesized that there would be differences in the rate of acquisition of antibodies to different antigens and how well they are boosted by infection, which impacts the acquisition of immunity. We examined responses to a range of merozoite antigens in 2 different cohorts of children and adults with different age structures and levels of malaria exposure. Overall, antibodies were associated with age, exposure, and active infection, and the repertoire of responses increased with age and active infection. However, rates of antibody acquisition varied between antigens and different regions within an antigen following exposure to malaria, supporting our hypothesis. Antigen-specific responses could be broadly classified into early response types in which antibodies were acquired early in childhood exposure and late response types that appear to require substantially more exposure for the development of substantial levels. We identified antigen-specific responses that were effectively boosted after recent infection, whereas other responses were not. These findings advance our understanding of the acquisition of human immunity to malaria and are relevant to the development of malaria vaccines targeting merozoite antigens and the selection of antigens for use in malaria surveillance.
Keywords: Children; P. falciparum; Serosurveillance; Vaccines